Enhanced Output Performance of All-Solution-Processed Organic Thermoelectrics: Spray Printing and Interface Engineering - Hwang, Seongkwon; Jeong, Inho; Park, Juhyung; Kim, Jae-Keun; Kim, Heesuk; Lee, Takhee; Kwak, Jeonghun; Chung, Seungjun (American Chemical Society, 2020)
We report two organocompatible strategies to enhance the output performance of all-solution-processed poly(3,4-ethylenedioxythiophene):poly-(styrenesulfonate) (PEDOT:PSS) thermoelectric generators (TEGs): introducing an additive spray printing process and functionalized polymer interlayers to reduce the module resistance. The spray printing enabled the deposition of 1-mu m-thick PEDOT:PSS layers with a high degree of design freedom, resulting in a significantly reduced sheet resistance of 16 Omega sq(-1) that is closely related to the thermoelectric output performance. Also, by inserting an ultrathin silane-terminated polystyrene (PS) interlayer between the PEDOT:PSS thermoelectric layers and inkjet-printed Ag interconnects selectively, the contact resistivity extracted by the transmission line method was reduced from 6.02 x 10(-2) to 2.77 x 10(-2) Omega cm(2). We found that the PS interlayers behaved as a thin tunneling layer, which facilitated the carrier injection from the inkjet-printed Ag electrodes into the PEDOT:PSS films by field emission with an effectively lowered energy barrier. The activation energy was also extracted using the Richardson equation, resulting in a reduction of 2.59 +/- 0.04 meV after the PS treatment. Scalable plastic-compatible processability and selective interface engineering enabled to demonstrate the flexible 74-leg PEDOT:PSS TEGs exhibiting the open-circuit voltage of 9.21 mV and the output power of 2.23 nW at a temperature difference of 10 K.
Keywords: ENERGY; PEDOTPSS; FILMS; POWER; CONDUCTIVITY; PARAMETERS; POLYMERS; SOLVENT; LAYER